METODE PREDIKSI POTENSI DAERAH IKAN MENGGUNAKAN CITRA AQUA MODIS DAN PENDISTRIBUSIAN HASIL DENGAN MENGGUNAKAN WEB (Studi Kasus : Perairan Selatan Jawa Timur - Bali) - Santoso, Budi; Sukojo , Bangun Muljo (GEOID, 2010)
Indonesia is a maritime country. Where one of the fishing production area is Southern region of East Java – Bali. For that this research is required in determining area which is have fishing potential. One of its parameter is oceanography obtained through the direct measurement or satellite remote sensing data extraction. Satellite imagery used in regional mapping of territorial water of Indonesia, for example NOAA-AVHRR, TERRA, and AQUA. In this research using AQUA satellite bringing multispectral sensors and also Vector Map of Indonesia. In processing of this AQUA MODIS imagery got the result of geometric correction with the average value equal to 0.229 and assess the SOF equal to 0.000722. Interpretation method done based on potential characteristic. Result obtained in this research show the prediction of potential fishing area. At southern region of East Java – Bali, there are its chlorophyll concentration 0.5-1.0mg.m3, while the temperature at front area is about 27-30oC which have potency of Madidihang, Tenggiri and Cakalang. The final result from this research is Prediction of Potential Fishing Ground Map and need to distribute using website which is able to downloaded by whom, especially the fisherman.